Evaluasi pemilihan teknologi Co-firing Biomassa pada PLTU batu bara dengan Metode Analytical Hierarchy Process (Studi Kasus: PLTU XYZ) - Irwan Aufi; Joko Wintoko; Nur Aini Masruroh (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2023)
Biomass co-firing technology is one way to accelerate the transition to renewable energy in Indonesia. Co-firing is currently used for the mixed combustion of coal and biomass in steam power plants with a certain blending ratio. One of the PLTU’s that has implemented co-firing technology in Indonesia is PLTU XYZ. However, as the co-firing technology progresses, PLTU XYZ experiences a number of problems, both in technical and non-technical areas. This study aims to evaluate the most appropriate co-firing technology that can be used for PLTU XYZ. The method used in this study is the Analytical Hierarchy Process (AHP). The results of this study indicate that the most effective criteria are economic and environmental, with weights of (0.4383) and (0.3024) followed by technical (0.1904) and social (0.0689). The most appropriate biomass co-firing technology currently used for PLTU XYZ is direct co-firing with the highest weight (0.7080) followed by indirect co-firing (0.1753) and parallel co-firing (0.1165).